Earthquake Hazard Impact and Urban Planning - Bostenaru Dan, Maria; Armas, Iuliana; Goretti, Agostino; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
The classical field dealing with earthquakes is called “earthquake engineering” and considered to be a branch of structural engineering. In projects dealing with strategies for earthquake risk mitigation, urban planning approaches are often neglected. Today interventions are needed on a city, rather than a building, scale. This work deals with the impact of earthquakes, including also a broader view on multihazards in urban areas. Uniquely among other works in the field, particular importance is given to urban planning issues, in conservation of heritage and emergency management. Multicriteria decision making and broad participation of those affected by disasters are included.
Part I: Urban hazard, exposure and vulnerability -- Part II: Earthquake risk assessment -- Part III: Risk management -- Part IV Impact and Decision making tools.
Keywords: Natural disasters; Environmental management; Regional planning; Urban planning; Natural Hazards; Environmental Management; Landscape/Regional and Urban Planning